Lignin improves release behavior of slow‐release fertilizers with high content of urea. Issue 47 (17th July 2019) - Gu, Haifeng; Zhang, Yuchao; Li, Xian; Li, Wenzhuo; Huang, Shuaiyu
ABSTRACT: To develop a slow‐release fertilizer with high content of urea, lignin was heated with urea–montmorillonite (M/U) extruded composites to synthesize a novel composite‐lignin/montmorillonite/urea (L/M/U). Mechanical test results of the composites showed that the L/M/U exhibited a greater flexure strength and a higher elastic modulus than the unmodified M/U extruded material. Based on the results of the urea release experiments, in the M/U extruded composites, the material with a high urea content exhibited a high urea release rate. By contrast, although the urea content of the 2:1:4 L/M/U formulation was higher than the 2:1:1 and 2:1:2 L/M/U formulations, the former formulation exhibited a lower urea release rate than the latter two formulations. The urea cumulative release (34.6%) of the L/M/U 2:1:4 after 105 h was also lower than that (93.7%) of the M/U 1:1 although the W urea (57.1 wt %) in the former was higher than the W urea (50.0 wt %) in the latter. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48238. Abstract : Lignin wrapped around the surface of the urea‐montmorillonite extruded composites, which retarded the release behavior of urea from the extruded composite.